2001
DOI: 10.1007/s00109-001-0295-1
|View full text |Cite
|
Sign up to set email alerts
|

Replication-selective viruses for cancer therapy

Abstract: Advances in our understanding of the molecular basis of cancer and the availability of technology to genetically engineer viruses have led to the development of replication-competent viruses to treat cancer. In theory, replication-selective viruses offer several appealing properties as biological agents for cancer therapy: they kill tumor cells selectively, and their replication leads to amplification of their oncolytic potential. Most preclinical experiments in tissue culture and in animal models support this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(53 citation statements)
references
References 95 publications
0
52
0
1
Order By: Relevance
“…4,5 Adenovirus dl1520, with deletion of E1B55K, selectively replicates in cancer cells presumably because of p53 deficiency in these cells. 20,21 However, recent studies showed that dl1520 could also replicate in cells expressing WT p53.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 Adenovirus dl1520, with deletion of E1B55K, selectively replicates in cancer cells presumably because of p53 deficiency in these cells. 20,21 However, recent studies showed that dl1520 could also replicate in cells expressing WT p53.…”
Section: Discussionmentioning
confidence: 99%
“…High levels of p53 lead to cell growth arrest or apoptosis that is presumed to inhibit viral replication. [3][4][5] Adenoviruses (Ad) have developed measures to overcome host cell apoptosis. The E1b-encoded E1B19K and E1B55K proteins protect the infected cells from these E1A-induced p53 effects.…”
Section: T O Induce the Cells Into S-phase For Effective Viralmentioning
confidence: 99%
“…Clinical trials have shown that dl1520 as a single anticancer agent cannot efficiently inhibit tumor growth. [50][51][52] One possible explanation for the limited efficacy of dl1520 in the clinical treatments is that some cancer cells within tumors may be resistant to dl1520 replication, just as some established cancer cell lines are resistant to dl1520 replication. Cancer cells that are resistant to viral replication will survive the treatment and continue its growth.…”
Section: Adenoviruses-induced Cell Cycle Changes In Hep3b and Saos2 Cmentioning
confidence: 99%
“…The use of a virotherapy, which employs a conditionally replicative adenovirus, allows the selective replication of virus in target cell types and permits subsequent rounds of viral amplification to greatly increase the antitumor effect. [8][9][10] One of the first examples of an oncolytic adenovirus was Onyx-015, an E1B 55 kDa gene deleted adenovirus, that was designed to replicate exclusively in p53-deleted or mutated tumor cells and has shown encouraging results in clinical trials. 11 Tissue-and tumor-specific promoters have also been incorporated in oncolytic viral vectors to drive selective expression of genes required for viral replication in tumor cells.…”
mentioning
confidence: 99%